Parameters optimization filter for signal processing USB keyboard enamation comprimising - Hao, Nguyen Ngọc Vinh; Chinh, Bui Duc; Minh, Ngo The (Journal of Science and Technology on Information security, 2022)
Abstract— Computer peripherals such as monitors, keyboards can be targets to exploit information through electromagnetic radiation side chanel attacks. In order to be able to perform these attacks on these devices, it is necessary to use appropriate digital filters to select the frequency band and reduce the effect of noise on the useful radiated signal. The article will introduce the parameter optimization process of the digital filter in recovering keystrokes from the radiated signal of the USB keyboard.